2016
DOI: 10.1177/1066896916652221
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Expression in Ectomesenchymal Chondromyxoid Tumor of the Anterior Tongue

Abstract: Ectomesenchymal chondromyxoid tumor (ECT) is a rare benign tumor of uncertain lineage, which almost exclusively affects the anterior tongue. Herein, we report 2 cases of ECT occurring in 58- and 56-year-old males on the right and on the left side of the dorsum of the anterior tongue, measuring 18 mm and 10 mm, respectively. Despite positive resection margin in one case, none of the tumors recurred during follow-up of 6 and 5 years. Microscopically, both tumors had lobular architecture with a mixture of solid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
1
20
0
2
Order By: Relevance
“…Yoshioka et al 24 were able to confirm the origin of ECT in ectomesenchymal cells derived from neural crest by demonstrating the expression of homeobox protein-transcription factor (Nanog), GFAP and microtubule associated protein 2 (MAP2) in cell cultures and positivity for octamer binding protein 3/4 (OCT3/4), transcription factor Sox2, Nanog, MAP2 and CD 105mRNAs in real-time polymerase chain reaction (RT-PCR) analysis. Moreover, with immunohistochemical methods, Laco et al 30 showed expression of transcription factor Sox10 in one of their two cases, so supporting the proposed neural crest theory.…”
Section: Review Of the Literaturementioning
confidence: 75%
See 1 more Smart Citation
“…Yoshioka et al 24 were able to confirm the origin of ECT in ectomesenchymal cells derived from neural crest by demonstrating the expression of homeobox protein-transcription factor (Nanog), GFAP and microtubule associated protein 2 (MAP2) in cell cultures and positivity for octamer binding protein 3/4 (OCT3/4), transcription factor Sox2, Nanog, MAP2 and CD 105mRNAs in real-time polymerase chain reaction (RT-PCR) analysis. Moreover, with immunohistochemical methods, Laco et al 30 showed expression of transcription factor Sox10 in one of their two cases, so supporting the proposed neural crest theory.…”
Section: Review Of the Literaturementioning
confidence: 75%
“…However, stimulated by previous genetic examinations on soft tissue myoepithelial tumors 35 Argyris et al 29 successfully demonstrated rearrangement or gain of Ewing sarcoma breakpoint region 1 (EWSR1) in 3 of 11 and 8 of 9 ECTs, respectively, whereas Laco et al 30 failed to find an EWSR1 rearrangement in two such tumors.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, as in previous studies, the present tumor was positive for S100 and GFAP, 4,6,7,12,15,19,23,26,27 demonstrating an origin from the neural crest, as well as for CD10, 28 NSE 20,29 and cyclin D1. 4,17,28 Regarding this last protein, strong nuclear ex-pression was detected, but no translocation of CCND1/IGH or amplification of the CCND1 gene was found. 28 No CD56 staining was observed, which is in agreement with a previous study 21 that reported a variable expression of this marker in its cases.…”
Section: Discussionmentioning
confidence: 96%
“…4,17,28 Regarding this last protein, strong nuclear ex-pression was detected, but no translocation of CCND1/IGH or amplification of the CCND1 gene was found. 28 No CD56 staining was observed, which is in agreement with a previous study 21 that reported a variable expression of this marker in its cases. An interesting finding of the present case was the high proliferative index identified by Ki-67 staining.…”
Section: Discussionmentioning
confidence: 96%
“…All NUT-positive tumors detected by IHC were further tested for NUT gene rearrangement. FISH was performed as previously described [17,18]. Briefly, 4-μm-thick section was routinely deparaffinized, incubated in the Heat Pretreatment Solution Citric (pH 6.0) (ZytoVision GmbH, Bremerhaven, Germany) for 15 min at 98 °C and digested in protease solution with Pepsin Solution (ZytoVision) at 37 °C for 5 min.…”
Section: Clinicopathological Datamentioning
confidence: 99%